Optimizing dark chocolate production: Effect of conching time, berry by-products, and sacha inchi oil on antioxidant attributes - Marleni Medina-Mendoza; Diner Mori-Mestanza; Roberth E. Iliquín-Fernández; Ilse S. Cayo Colca; Efraín M. Castro-Alayo; César R. Balcázar-Zumaeta (Journal of Agriculture and Food Research)
This study aimed to develop dark chocolates enriched with freeze-dried berry by-products (FD) from goldenberry (Physalis peruviana) and blackberry (Rubus floribundus), as well as sacha inchi oil (SIO), by employing varying conching times (CT). Response Surface Methodology (RSM) was utilized to evaluate the effects of CT (16, 20, and 24 h), FD concentration (2 %, 6 %, and 10 %), and SIO levels (1 %, 3 %, and 5 %) on the physicochemical properties of the chocolates. Results revealed that CTs of 16 and 20 h, combined with higher SIO concentrations (5 %), significantly enhanced antioxidant activity. Among the formulations, blackberry-enriched chocolate achieved the highest DPPH and ABTS antioxidant values, measuring 518.0 and 200.7 μmol Trolox/g D.W., respectively. The highest total phenolic content was observed with the addition of 10 % FD and 5 % SIO after 16 h of conching. Key interactions between CT and ingredient composition (FD and SIO) significantly influenced rheological properties, texture, and particle size distribution. These findings underscore the potential of integrating nutrient-rich natural ingredients and utilizing RSM to optimize the production of functional dark chocolates with enhanced antioxidant attributes.